Systemic dysregulation of the gut microenvironment plays a pivotal role in the onset and progression of inflammatory bowel disease - Kou, Ruilong; Guo, Yonggang; Qin, Zhiwei; Xu, Xiaochen; Liu, Yihao; Wei, Wenqin; Chen, Yu; Jian, Zhiyuan; Lan, Bin (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD) represents a multifaceted, chronic inflammatory condition affecting the gastrointestinal tract, with its underlying pathophysiological mechanisms not yet fully elucidated. Recent research has underscored the pivotal role of the gut microenvironment, a complex ecological system, in the pathogenesis of IBD. This review systematically examines the interactions between gut microenvironment components and their roles in the pathogenesis of IBD. It is now understood that gut dysbiosis results in a decrease in beneficial microbiota, such as Faecalibacterium and Roseburia, along with an increase in pathogenic bacteria, including Adherent-invasive Escherichia coli (AIEC). This microbial imbalance results in a reduction in the production of beneficial metabolites, such as short-chain fatty acids, and the accumulation of detrimental metabolites, thereby directly disrupting the gut microbiome. The resultant gut dysbiosis leads to dysfunction in intestinal stem cells (ISCs) and a reduction in the expression of tight junction (TJ) proteins, thereby further compromising the integrity of the intestinal epithelial barrier. This dysfunction allows microorganisms and harmful metabolites to penetrate the barrier, reaching the submucosal layer, where they activate both innate and adaptive immune responses, thereby initiating a complex immune cascade. Over time, this process leads to a self-sustaining inflammatory cycle that culminates in chronic IBD and potentially contributes to the development of metabolic disorders. This paper examines this cycle, elucidating the interactions among gut microbiota dysbiosis, metabolite alterations, barrier dysfunction, and immune activation that drive the pathogenesis of IBD, while also critically assessing the limitations of current therapeutic strategies. Based on our understanding of the overarching dysregulation of the gut microenvironment, we propose a paradigm shift in IBD from “controlling inflammation” to “restoring intestinal homeostasis”, and from “single therapy” to “comprehensive intervention”. This integrated approach encompasses microbiome remodeling, metabolite intervention, reconstruction of the immune microenvironment, and repair of barrier function. Such a multidimensional and integrated therapeutic strategy promises to effectively disrupt the pathological feedback loop, restore gut homeostasis, and offer novel theoretical and clinical insights for the precise treatment of IBD and its progression.